Effect of continuous positive airway pressure in hypertensive patients with obstructive sleep apnea and high urinary metanephrines. Issue 1 (January 2018) - Gilardini, Luisa; Lombardi, Carolina; Redaelli, Gabriella; Mattaliano, Paola; Fanari, Paolo; Cornacchia, Mauro; Scacchi, Massimo; Mai, Stefania; Ferronato, Patrizia; Parati, Gianfranco; Invitti, Cecilia
Abstract : Objective: Some cases of pseudopheochromocytoma have been described among hypertensive patients with obstructive sleep apnea (OSA). This study examined whether a pathological rise of urinary metanephrines is a common feature in hypertensive OSA patients and, in such a case, whether the ventilation treatment during sleep (continuous or biphasic positive airway pressure) may normalize high metanephrines levels. Methods: Patients with endocrine diseases, drug abuse, therapy with TCA and cardiovascular events in the previous 6 months were excluded. Thirty-four hypertensive patients with OSA (BMI 40.6 ± 8.7 kg/m 2 ) performed three 24-h urine collections for metanephrine assessment, before and after 1 month of ventilation therapy. Results: Urinary normetanephrine (uNMT) was above the normal limit in 21 of 34 of the patients. In the 16 to 21 patients with high uNMT who were compliant to ventilation treatment, uNMT decreased in 13 by 26% and normalized in six of 13. uNMT levels were associated with apnea hypopnea index (AHI) ( r  = 0.799, P  < 0.0001) and minimal SaO2 ( r  = −0.700, P  < 0.01). The ventilation therapy-induced changes in AHI were associated with those in uNMT ( r  = 0.689, P  < 0.005). In the multivariate analysis with uNMT changes as dependent variable and changes in AHI, BMI, SBP as independent variables, only AHI changes were independently associated with uNMT changes (β = 0.738, P  < 0.01). Conclusion: Two-thirds of OSA hypertensive patients have uNMT values above the normal limit. The early identification of these patients is important as ventilation therapy can correct the pathological sympathoadrenal activation. Patients who do not normalize uNMT with ventilation therapy deserve a strict follow-up as this lack of normalization may indicate insufficient ventilation therapy or resistance of sympathetic hyperactivity to this treatment, not excluding an early stage of a chromaffin tumor. Abstract : Supplemental Digital Content is available in the text